2004
DOI: 10.1142/s0192415x04002089
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and Therapeutic Effects of Acupuncture on Bone Mass in Osteopenic Ovariectomized Rats

Abstract: This study was designed to (1) test the preventive and therapeutic effects of acupuncture on osteopenia in ovariectomized (OVX) rats, and (2) assess whether treatment of different acupuncture points causes different effects on tibiae, femora or lumbar spines. Thirty-five female Sprague-Dawley rats were divided into four groups: Sham (sham-operated, non-acupuncture); Model (OVX, non-acupuncture); Acp-A [OVX, bilateral needling of points Tsu-San-Li (ST-36) and San-Yin- Chiao (SP-6)]; and Acp-B (OVX, bilateral ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Acupuncture is believed to be able to stimulate bone healing using points that tonify and move Qi along the meridians that pass through the affected area [13]. Previous studies have shown the beneficial effects of acupuncture on bone healing [14][15][16]. In dogs with experimental radial defect, Sharifi et al [14] showed that acupuncture treatment of 14 days, 10 min/day has positive and stimulatory effects on formation of callus, trabecule, and fibrocartilage, compared to a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture is believed to be able to stimulate bone healing using points that tonify and move Qi along the meridians that pass through the affected area [13]. Previous studies have shown the beneficial effects of acupuncture on bone healing [14][15][16]. In dogs with experimental radial defect, Sharifi et al [14] showed that acupuncture treatment of 14 days, 10 min/day has positive and stimulatory effects on formation of callus, trabecule, and fibrocartilage, compared to a control group.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs with experimental radial defect, Sharifi et al [14] showed that acupuncture treatment of 14 days, 10 min/day has positive and stimulatory effects on formation of callus, trabecule, and fibrocartilage, compared to a control group. Acupuncture has been reported to increase bone weights, bone strength, trabecular volume, and bone formation rate in osteopenic ovariectomized rats [15][16][17][18]. And it has also been reported that acupuncture at acupoints has stronger effects on bone healing than at nonacupoints, indicating point-specificity on bone healing [17].…”
Section: Discussionmentioning
confidence: 99%
“…4,17,18 For example, BL 23 is an acupoint on the BL, located inferior and lateral to the spinous process of the second lumbar spine, used frequently in the management of menopausal hot flashes and osteoporosis. 4,17,18,33,34 Acupuncture at BL 23 has been shown to be effective in promoting bone formation, improving bone architecture, and reversing osteoporosis in the mice model. 33,34 These effects were suggested in relation to some degree of enhancement in the secretion of sex hormone and declining bone turnover by decreased OC levels.…”
Section: Chien Et Almentioning
confidence: 99%
“…4,17,18,33,34 Acupuncture at BL 23 has been shown to be effective in promoting bone formation, improving bone architecture, and reversing osteoporosis in the mice model. 33,34 These effects were suggested in relation to some degree of enhancement in the secretion of sex hormone and declining bone turnover by decreased OC levels. 33,34 There has been no report Change from baseline was defined as (score at 10th week -baseline score)/baseline score.…”
Section: Chien Et Almentioning
confidence: 99%
“…Fat emboli and/or thrombi may further compromise circulation to the femoral head [5]- [7]. In addition, repair capacity and bone remodeling play important roles in the progression and severity of nontraumatic ONFH [8].…”
Section: Introductionmentioning
confidence: 99%